Analysis of Erythrocyte Sedimentation Rate Levels in Active-Smoking Students: A Survey of Papuan Students in Bandung City - Yogobi, Kesya; Sudrajat, Agus (Dinasti Health and Pharmacy Science, 2025)
Smoking is a high-risk behavior commonly found among university students, including Papuan students residing in Bandung City. Exposure to toxic substances in cigarettes can trigger inflammatory processes, which can be detected through an increase in the Erythrocyte Sedimentation Rate (ESR). This study aims to describe the ESR values of Papuan students who are active smokers and to examine their relationship with smoking duration. This research used a descriptive quantitative design with purposive sampling involving 30 respondents, whose ESR levels were measured using the Westergren method. The results showed that ESR values ranged from 12 to 45 mm/hour, with an average of 26.7 mm/hour. A total of 63.3% of respondents had elevated ESR levels (>20 mm/hour), while 36.7% were within the normal category. Respondents who had been smoking for more than three years had higher ESR levels compared to those who had been smoking for less than three years. This study concludes that most Papuan students who are active smokers experience elevated ESR levels, indicating the presence of inflammatory processes associated with smoking habits.